A cluster of methylations in the domain IV of 25S rRNA is required for ribosome stability - Gigova, Andriana; Duggimpudi, Sujitha Smruthy; Pollex, Tim; Schaefer, Matthias R.; Koš, Martin (RNA, 2014)
In all three domains of life ribosomal RNAs are extensively modified at functionally important sites of the ribosome. These modifications are believed to fine-tune the ribosome structure for optimal translation. However, the precise mechanistic effect of modifications on ribosome function remains largely unknown. Here we show that a cluster of methylated nucleotides in domain IV of 25S rRNA is critical for integrity of the large ribosomal subunit. We identified the elusive cytosine-5 methyltransferase for C2278 in yeast as Rcm1 and found that a combined loss of cytosine-5 methylation at C2278 and ribose methylation at G2288 caused dramatic ribosome instability, resulting in loss of 60S ribosomal subunits. Structural and biochemical analyses revealed that this instability was caused by changes in the structure of 25S rRNA and a consequent loss of multiple ribosomal proteins from the large ribosomal subunit. Our data demonstrate that individual RNA modifications can strongly affect structure of large ribonucleoprotein complexes.
Gesehen am 22.07.2020